Intensity of fruit thinning in peaches 'Flordaprince' conducted in orchard of high density - Filho, João Aleixo Scarpare; Minami, Keigo; Kluge, Ricardo Alfredo (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this paper was to test the behavior of peaches (Prunus persica (L.) Batsch.) cultivar Flordaprince carried out in high dense orchard (3,333 plants/ha) submitted to different intensities of hand thinning of fruits. The treatments tested were 120, 100 and 80 fruits per plant and without thinning (230 fruits per plant). The thinned plants produced larger and weightier fruits if compared with control plants. The yield per plant (kg) and estimated productivity (ton/ha) were higher in plants not thinned, but marketing classification and gross income were lower in this treatment due to small fruit size and weight. The treatments 100 and 80 fruits per plant (56.52% and 65.21% of thinning, respectively) presented the best results.
Keywords: hand thinning; defruiting; productivity; meadow orchard; Prunus persica